2004
DOI: 10.1111/j.1356-9597.2004.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

The endoplasmic reticulum stress response is stimulated through the continuous activation of transcription factors ATF6 and XBP1 in Ins2+/Akita pancreatic β cells

Abstract: The dominant C96Y mutation of one of the two murine insulin genes, Ins2 , causes diabetes mellitus in 'Akita' mice. Here we established pancreatic islet β β β β cell lines from heterozygous mice ( Ins2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(131 citation statements)
references
References 44 publications
8
121
1
1
Order By: Relevance
“…Further support for a role of ER stress in diabetes was presented in mice with genetic ablation of PERK or the chaperone P58 IPK that resulted in islet beta cell death and hyperglycaemia [35,36]. Moreover, a recent study has shown that in the Akita mouse model of diabetes, a mutation in Ins2 resulted in misfolding of the insulin protein causing ER stress and beta cell apoptosis [37]. Chronic exposure of islets and beta cells to fatty acids is known to cause dysfunction and cellular death [38], and this apoptosis has recently been shown to be the result of activation of an ER stress response [39][40][41].…”
Section: Possible Mechanisms That Could Explain Hypersecretion-inducementioning
confidence: 98%
“…Further support for a role of ER stress in diabetes was presented in mice with genetic ablation of PERK or the chaperone P58 IPK that resulted in islet beta cell death and hyperglycaemia [35,36]. Moreover, a recent study has shown that in the Akita mouse model of diabetes, a mutation in Ins2 resulted in misfolding of the insulin protein causing ER stress and beta cell apoptosis [37]. Chronic exposure of islets and beta cells to fatty acids is known to cause dysfunction and cellular death [38], and this apoptosis has recently been shown to be the result of activation of an ER stress response [39][40][41].…”
Section: Possible Mechanisms That Could Explain Hypersecretion-inducementioning
confidence: 98%
“…Mouse pancreatic β cell lines carrying the Ins2 +/+ and Ins2 +/Akita genes were cultured as described previously (Nozaki et al, 2004). HeLa, mouse L929, NIH 3T3, and BALB/c 3T3 cells were cultured in Dulbecco's modified essential medium supplemented with 10% fetal bovine serum.…”
Section: Cell Culturementioning
confidence: 99%
“…The ERSE-II sequence on the ARMET promoter was disrupted by site-directed mutagenesis. The effector construct containing mouse wild-type Ins2 and its C96Y mutant was described previously (Nozaki et al, 2004). The reporter gene constructs driven by the human wild-type and ERSE-disrupted GRP78 promoters were described previously (Yoshida et al, 1998).…”
Section: Construction Of Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, in the Akita mouse, diabetes resulted purely as a consequence of insulin misfolding leading to ER stress in the absence of any defect of insulin production or sensitivity, showing that ER stress can play a causal role in diabetes development. Cell lines established from ␤-cells of these mice exhibited continuous activation of the master regulators of the ER stress response, ATF6 and XBP1 (24). Examination of postmortem sections of pancreata from normal compared with type 2 diabetic subjects showed up-regulation of ER stress markers, including BiP, DnaJC3 (p58 IPK ), and CHOP in the pancreata from diabetic subjects (23).…”
mentioning
confidence: 99%